Hubungan Parental Behavioral Control dengan Obsessive Internet Passion Pada Generasi Z - Rahmi Yulianti; Djudiyah Djudiyah; Udi Rosida Hijrianti (Jurnal Ilmiah Psikologi Candrajiwa, 2021)
Many Indonesians are already connected to the internet. Apart from the benefits, of course there are also detriment caused by the internet, especially if it is used excessively. Generation Z is a generation that grew up at the same time as the internet, has certainly experienced more impacts than previous generations. The purpose of this study was to determine the correlation between parental behavioral control and obsessive internet passion in Generation Z. This research is a quantitative correlational study. The research subjects were Generation Z, who are still at school age, born in 2004-2009 and live with their parents, the samples were selected using non-probability sampling with incidental sampling technique (convenience sampling). The instruments used to collect the data in this study were Parental Control Scale (PCS) and Obsessive Passion Scale (OPS). The data that was analyzed using Karl Pearson's product moment correlation with the help of SPSS version 23 shows that there is a significant negative relationship between parental behavioral control and obsessive internet passion in generation Z which shown by product moment test results with r value of -0.606 and p value of 0.000 (p < 0,01).